The relationship of dental caries and dental fear in Malaysian adolescent: a latent variable approach - Esa, R.; Ong, A.L.; Humphris, G.; Freeman, R. (BioMed Central, 2014)

(untitled)
Background To investigate the role of geography (place of residence) as a moderator in the relationship between dental caries disease and treatment experience and dental fear in 16-year-olds living in Malaysia.